Prinsip Good Governance dan Kritik atas Rasionalitas: Diskursus Pengelolaan Tunjangan Anggota DPR RI dalam Membentuk Persepsi Keadilan Publik - Jazmine, Indira; Roring, Edward Benedictus; Tholemadia, Finnova Khairullah; Simbolon, Augustha; Samekto, FX Adji (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study analyzes the empowerment of members of the Indonesian House of Representatives (DPR RI) through the perspectives of constitutional law and mass psychology, highlighting its impact on public perceptions of justice. Through a framework of understanding the principles of good governance, this study assesses aspects of transparency, accountability, and participation in granting permits. Normatively, allowances should reflect public ethics and social justice, but empirically, they actually give rise to dissatisfaction and negative perceptions due to economic disparity and poor legislative performance. Using a qualitative-descriptive approach, the study finds that weak implementation of good governance principles reinforces polarization and erodes public trust, resulting in allowances being perceived as a form of injustice.